Terceira lavas isotopic signatures and multi-scale mantle heterogeneity at the Azores Archipelago - Madureira, Pedro (2011)
Terceira Island mafic lavas (< 30 ka), erupted from two main active volcanic systems, were analysed in this study: Fissural zone (F), interpreted as the sub aerial expression of the Terceira Rift, and Sta Bárbara central volcano (SB), which dominates the western topography of the island. These mafic lavas present a significant elemental range, with SB (Mg# <50) being generally more evolved than F (typically Mg# >50). However, if fractional crystallization explains the intra-system variability, it cannot be considered responsible for some chemical differences between those 2 volcanic systems. This is clearly demonstrated by distinct Ba/Th (200 vs. 80), Ce/Th (35 vs. 25) and 206Pb/204Pb ratios (19.93 19.99 vs. 19.34 -19.85), which clearly point to a heterogeneous mantle source. Terceira magmas formed from sources characterized by time-integrated depletion (εNd: 5.4 to 6.4; εHf: 7.7 to 10.7) significantly more marked than the observed for coeval lavas outcropping in the neighbouring islands of Pico and S. Miguel, the later also formed in relation with the Terceira Rift. In opposition Terceira is characterized by more radiogenic Pb isotopic ratios indicating a stronger HIMU presence at its source. From elemental reasoning, SB magmas were generated by lower % of partial melting being also characterized by higher 206Pb/204Pb ratios. This indicates that the HIMU domains of mantle source were preferentially sampled during the lower degree melting events. Considering the positioning of Terceira samples below the NHRL and the negative correlation between Nb/U and 206Pb/204Pb, the development of HIMU signatures is a relatively recent event. Our data strengthen the heterogeneous character of the sub-Azores mantle, which is evident even when mantle is sampled along the same structure (Terceira Rift) and, also, at the scale of an individual island.